SOME NEW OSTROWSKI TYPE FRACTIONAL INTEGRAL INEQUALITIES FOR BETA (r, g)-PREINVEX FUNCTIONS VIA CAPUTO k-FRACTIONAL DERIVATIVES - Kashuri, Artion; Liko, Rozana; Du, Ting-Song (Matematichki Bilten, 2019)
In the present paper, the notion of beta \((r,g)\)-preinvex function is applied to establish some new generalizations of Ostrowski type integral inequalities via Caputo \(k\)-fractional derivatives.